Overload injuries in barefoot/minimal footwear running: evidence from crowd sourcing - Daumer, Martin; Kleinmond, Christine; Stolle, Christoph; Lederer, Christian; Hilgers, Marc; Walther, Markus (PeerJ PrePrints, 2014)
Background: The incidence of injuries in minimal footwear or barefoot runners compared to runners using conventional running shoes is still being discussed. Methods: We focus here on methods and results of a online survey in a community of minimal footwear/barefoot (MF/B) runners. The aim of the survey was to investigate the viability of the method and to record first insights on running behavior, distance performance and injuries. Results: In total 226 runners answered the questionnaire, 15 subjects had to be removed due to invalid data. A total of 211 (94%) subjects (152 male, ages 15-71 years [mean=40]) were included in the analysis. The risk to suffer a running related injury was significantly increased during the time period of changing from shod running to MF/B running (see Table 2). The injury rate per km was markedly lower – about one half - in MF/B than in shod running, but threefold higher during the transition period. Discussion/Conclusion: Future research into the right “dosage” of barefoot/minimal footwear running in the transition period is warranted. We speculate that special adaptations - which may take years and thousands of kilometers to become effective - of the neuromuscular control play a major role, very similar to the thousands of hours a person needs to play and practice playing the piano before becoming a musician.
Keywords: natural running; running injuries; barefoot running; crowd sourcing